Bismillahs and Beginnings: Notes from the Islamicate on ReOrienting Classicism - Marchella Ward (ReOrient, 2025)
The story of the relationship between ancient (so-called “classical”) Greece and Rome and modern Europe is usually told as if it were a genealogy. It is common both inside and outside the academic study of the ancient world to hear this genealogy described as the “classical tradition”. This imagined connection reifies European supremacy and has the effect of naturalising an orientalist, Islamophobic, and racist world narrative that distances the “West” from the “East” on grounds of differential proximity to the classical and excludes Islam from its family tree entirely. This world narrative holds sway even in spite of studies that have attempted to expand “the classical” beyond the so-called West, such as – for instance – those that seek to unearth a connection between the literatures of ancient Greece and of the “Near East”. Such studies are particularly useful for thinking about the relationship between classicism and orientalism, because even as they point Eastwards, they do so according to a “clash of civilisations” structuring of the world that is engendered by classicism’s genealogical narrative. Rather than attempting to show how classically influenced the Islamicate really is (which has been one way of constructing anti-orientalist refutations of this “clash of civilisations” structure), this article is an experiment aimed at finding out whether understanding the Muslim ontologically, as oppositional with Eurocentrism, might in fact be able to counter classicism and work for justice.